Concept Paper: A Virtual Centralized IRB System - McWILLIAMS, RITA; HEBDEN, CARL W.; GILPIN, ADELE M. K. (Accountability in research, 2006)
Context: As the volume and complexity of research have increased, the amount of time spent on Institutional Review Board (IRB) review has decreased. The complexity of research has expanded, requiring increasingly specialized knowledge to review it. Dilemma: Under the current system, increasing numbers of research studies requiring expertise in ethics, new technologies or diverse study designs place a substantial burden upon local IRBs and often result in substantial variability among their reviews. This lack of uniformity in the review process creates uneven human subjects' protection thus undermining the intent of the Common Rule. Objectives: To outline a scenario for expert centralized IRB review via implementation of a national virtual IRB review system overseen by the Office for Human Research Protections (OHRP). Conclusions: The complicated ethical issues and science involved in much of current research warrant an expert review panel. Centralized review would enable expert review specific to the research at hand, ensure consistency in human subjects protection, reduce the burden on local IRBs, and may reduce time spent obtaining approval. A centralized virtual system would allow IRB members to remain at their institutions while providing unprecedented expert review through currently available technology, and make information regarding monitoring and adverse event reporting available online in real-time. Dr. McWilliams, an epidemiologist, provided the original idea and wrote the article. Mr. Hebden provided the technological expertise for the article and edited the article. Dr. Gilpin provided legal and ethical expertise and edited the article.